2022
DOI: 10.3389/fmicb.2022.928139
|View full text |Cite
|
Sign up to set email alerts
|

Genus-Specific Interactions of Bacterial Chromosome Segregation Machinery Are Critical for Their Function

Abstract: Most bacteria use the ParABS system to segregate their newly replicated chromosomes. The two protein components of this system from various bacterial species share their biochemical properties: ParB is a CTPase that binds specific centromere-like parS sequences to assemble a nucleoprotein complex, while the ParA ATPase forms a dimer that binds DNA non-specifically and interacts with ParB complexes. The ParA-ParB interaction incites the movement of ParB complexes toward the opposite cell poles. However, apart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Next, based on the obtained BTH results, we set out to examine PapM interactions with ParA and DivIVA using protein colocalization assays in E. coli. Earlier, we have shown that EGFP-ParA colocalized at the poles of E. coli cells with mCherry-DivIVA when coproduced (Pióro et al 2018(Pióro et al , 2022.…”
Section: Papm Para and Diviva Form A Tripartite Complex Which Is Affe...mentioning
confidence: 69%
See 2 more Smart Citations
“…Next, based on the obtained BTH results, we set out to examine PapM interactions with ParA and DivIVA using protein colocalization assays in E. coli. Earlier, we have shown that EGFP-ParA colocalized at the poles of E. coli cells with mCherry-DivIVA when coproduced (Pióro et al 2018(Pióro et al , 2022.…”
Section: Papm Para and Diviva Form A Tripartite Complex Which Is Affe...mentioning
confidence: 69%
“…Upon interaction with segrosomes, ParA dimers hydrolyse ATP and are released from the nucleoid, while the ParB complex moves toward a higher concentration of the nucleoid-bound ParA (Lim et al 2014;Surovtsev, Campos, and Jacobs-Wagner 2016). Surprisingly, the ParAB-mediated segregation shows some bacterial species-specific features (Kawalek et al 2020;Pióro et al 2022;Pióro and Jakimowicz 2020). These differences involve the interactions of the segregation proteins with other proteins or protein complexes, like the cell elongation complex which governs polar cell extension in Actinobacteria, such as Mycobacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon interaction with segrosomes, ParA dimers hydrolyze ATP and are released from the nucleoid, while the ParB complex moves toward a higher concentration of the nucleoid-bound ParA ( 7 , 8 ). Surprisingly, the ParAB-mediated segregation shows some bacterial species-specific features ( 4 , 9 , 10 ). These differences involve the interactions of the segregation proteins with other proteins or protein complexes, like the cell elongation complex which governs polar cell extension in Actinobacteria, such as mycobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The unique features of mycobacterial chromosome segregation further include the interaction between ParA and DivIVA ( 9 , 34 , 37 ). Disruption of ParA-DivIVA binding results in modest segregation defects ( 37 ).…”
Section: Introductionmentioning
confidence: 99%